Bubble migration characteristics in power transformer oil under coupled stresses of forced vibration and electrical field - Niyomugabo Emmanuel Ladislas; Qingmin Li; Qiushi Liu; Wu Jie; Huang Weimin (IET Science, Measurement & Technology, 2023)
Abstract The stresses existing in power transformers lead to the generation of bubbles. They are the primary source that worsens and leads to insulation failure. Due to the complexity of bubble dynamics, it is challenging to figure out bubble mechanisms. However, creation, migration, and accumulation mechanisms require further explanation. A set of experiments has been conducted to provide a scientific overview of bubbles. The results revealed that buoyancy is dominant in low electric fields, while high electric fields affect bubbles' rise. Bubbles stretch and oscillate while moving. When the electric field is not strong, the AC field reduces the duration and volume of bubble detachment. Vibration stress on the other side is leading the bubble motion including detachment frequency and migration speed. Under the combination of AC and vibration stresses, the bubble distortion degree aggravates and bubble gathering formation is easy. This research can provide a deeper acumen of the bubble's actions beneath a power transformer under a combination of vibration and electric fields. It provides essential technique parameters to deal with while investigating bubble's problems and related engineering research areas.